Placemaking Through Time in Nepal: Conceptualising the Historic Urban-Rural Landscape of Kathmandu - Xiang Ren; Sangeeta Singh; Abhishek Bhutoria; Huriye Armağan Doğan (Urban Planning)
The ever-densifying and developing cities from the rapidly urbanising Global South are still facing severe socio-cultural challenges driven by the rapid urbanisation and tourism development, including the loss of architectural heritage, cultural memory, place identity, informal ecology, and economy in and around the historic urban landscape (HUL) particularly. Following the call for a “peri-urban turn” in recent geographical and urban studies, this article conceptually extends the established HUL framework to a broader historic urban–rural landscape (HURL) framework for the evolving and underrepresented territories of the Southern cities. It includes and interprets the local community’s placemaking practices and agency in the context of transitional rural-to-urban dynamics. Through ethnographic fieldwork in the historic environment of Kathmandu, Nepal, and by exploring the Basantapur area’s living heritage setting for the local community’s transient, rural, and ritual practices, this article develops an urban-anthropological interpretation of tangible and, of increasing relevance in the Global South contexts, intangible cultural heritage from the local community’s perspective, narratives, and agency. The article argues for a shift in focus from approaching the urban heritage buildings, urban–rural landscape, and intangible cultural heritage separately from the HUL which traces the past, to a more transitional, evolving, and layered HURL which anchors the present. It concludes with HURL’s methodological capacity to further close reading of Southern places through time and the lifeworld constituted and embedded in the placemaking practice beyond the Eurocentric tradition and paradigms.